Tourists' memories, sensory impressions and loyalty: In loco and post-visit study in Southwest Portugal - Agapito, Dora (2019)
This study aims to offer some insights on the contribution of sensory diversity as perceived by tourists to memorable destination experiences and to explore the connection between long-term memory of sensory impressions and destination loyalty. The vital role of the sensory dimension of tourist experiences is stressed by current tourism research and supported by a multidisciplinary view on the role of the five external senses in human perception, memory, and behavior. While the marketing management approach highlights the importance of considering multisensory information in the process of facilitating positive and memorable destination experiences, there is a lack of empirical research to validate the theoretical literature. A two-step exploratory study was conducted in loco and six months after tourists' visits to Southwest Portugal. The findings suggest that perceived richer sensory tourist experiences may have a significant role in the long-term memory of individuals' experiences, encouraging favorable tourist behavior towards destinations. (C) 2016 Elsevier Ltd. All rights reserved.